Parametric investigation on behaviour of carbon fiber reinforced polymers wrapped reinforced concrete columns under eccentric loads. Issue 8 (5th August 2022) - Fareed, S.; Ayub, L.; Khan, A.R.
Abstract: The use of carbon fiber reinforced polymer (CFRP) has proved to be significantly efficient in improving the overall behaviour of reinforced concrete columns. The use of high‐strength concrete in columns not only reduces the size but also gives adequate durability to the structure. The behaviour of reinforced concrete columns depends on numerous parameters, including concrete compressive strength, percentage of steel, cross‐section dimensions, ties spacing and the slenderness ratio. In this work the following parameters are investigated: Concrete compressive strength, percentage of steel, and the slenderness ratio. The focus of experimental investigation was to study the influence of carbon fiber reinforced polymer wrapping on the behaviour of plain concrete columns. Following the experimental investigation, a detailed numerical investigation was conducted to study the influence of the above parameters on the behaviour of eccentrically loaded plain and reinforced concrete columns. The influence of carbon fiber reinforced polymer wrapping on the overall performance was also studied using the available models for predicting the load‐moment interaction of columns to confirm the findings of the numerical investigations. Based on the detailed experimental and numerical investigation it was found that the concrete compressive strength significantly influences the overall behaviour of the reinforced concrete columns subjected to eccentric loadings. Abstract : Experimental and numerical investigations were conducted to study reinforced concrete columns under eccentric loadings. Furthermore, the influence of carbon fiber reinforced polymer wrapping was also studied. The overall behaviour of the reinforced concrete columns is significantly influenced by the parameters studied in this study experimentally and numerically.